In-Package Air Cold Plasma Treatment of Chicken Breast Meat: Treatment Time Effect - Hong Zhuang; Michael J. Rothrock Jr.; Kelli L. Hiett; Kurt C. Lawrence; Gary R. Gamble; Brian C. Bowker; Kevin M. Keener (Journal of Food Quality)
The objective of this study was to investigate the effects of in-package dielectric barrier discharge (DBD) atmospheric cold plasma (CP) on meat color, microbiological quality and safety of chicken breast meat (pectoralis major). Raw broiler breast meat was collected from a local commercial plant. Noninoculated meat samples and meat samples inoculated with Campylobacter and Salmonella were packed in polymeric trays with air. The packaged samples were CP-treated at 70 kV for different times (0, 60, 180, or 300 sec) and stored at 4°C for 5 days. Microbial counts (psychrophiles, Campylobacter, Salmonella) and meat color (International Commission on Illumination (CIE) L∗a∗b∗) were measured before CP treatments and after 5 days of posttreatment storage. Psychrophile growth was inhibited (P<0.05), and both food-borne pathogens were reduced (P<0.05) by more than 90% with CP treatments regardless of treatment time. No differences in pathogenic bacterial counts were observed between the three treatment times; however, increasing treatment time beyond 60 sec resulted in additional inhibition of psychrophilic growth. There were no differences (P>0.05) in a∗ and b∗ values between pretreatment and posttreatment plus storage; however, all CP treatments resulted in increased L∗ value (P<0.05). Results indicate that in-package CP treatments can be used to reduce both microbial spoilage and food-borne pathogen risks, which could increase microbial food safety, although it may result in an overall paler breast meat, and the reduction (about 1 log) in pathogenic and spoilage microbes are limited.